FORMAS DE LA DISIDENCIA. SINERGIAS ENTRE FORMA Y DISCURSO EN LOS FILMES DE TEMÁTICA SOCIAL DE NIEVES CONDE: EL CASO DE Surcos (1951) - Rubén HIGUERAS FLORES (Fonseca, Journal of Communication, 2023)
In the present text we intend to expose the fertile significant apparatus displayed in the social themed feature films directed by José Antonio Nieves Conde. Through the textual analysis of a paradigmatic film such as Surcos, we demonstrate the way in which the enunciative mechanisms forge and reinforce the discourse of the text, revealing an enunciative device of unusual richness and singular hybridity, whose images approach an apparently realistic register, taking paradoxically opposite aesthetic options as a reference in their high degree of stylization.